The Role of Social Conversation in Strengthening Social Media Literacy Among Gen Z - Adi Fahrudin; Evi Febriani; Deasyanti Deasyanti; Ida Hindarsah; Heri Erlangga; Rini Hartini Rinda Andayani; Nurul Hudani Binti Md. Nawi; Lailawati Bte Madlan @ Endalan; Norhamidah Binti Jarimal @ Safri; Hon Kai Yee (Smart Society, 2026)
Generation Z is a cohort of young people raised in the digital era, with social media playing a significant role in their social interactions and information consumption. This proximity creates opportunities for self-development, but also poses challenges in the form of exposure to unverified information, social pressure, identity formation in online spaces, and shifting patterns of social relationships. This Community Service (PkM) activity aims to facilitate students’ reflective awareness of life goals, career plans, social media literacy, and healthy social relationships through social conversation techniques. The activity was conducted at the Indonesian School of Kota Kinabalu (SIKK), Sabah, Malaysia, involving 30 students aged 15–17 years and 8 facilitators over 120 minutes. A participatory method was used through small group discussions, reflective questions, and open dialogue. The implementation of the social conversation approach provided a dialogic, safe, and participatory atmosphere that facilitated students’ critical reflection on their digital experiences. Students demonstrated emerging awareness of digital footprints, information verification, the relationship between social media and identity formation, and the psychosocial impact of social media use. These findings suggest that social media literacy is more meaningfully developed through a contextual, dialogic, and experience-based approach, rather than a one-way delivery of material. This social conversation model offers a replicable reference for community service practices aimed at strengthening digital literacy among Gen Z youth.